Introducing agroecology in primary schools: an independent impact evaluation in Uruguay. Issue 2 (7th February 2021) - Roscioli, Federico; Malerba, Daniele; Burchi, Francesco
ABSTRACT: This study evaluates the impact of an agroecological school gardening program on eating behavior, agroecological knowledge and educational capabilities of 9–12 year-old schoolchildren in Montevideo, Uruguay. The study uses a mixed method approach and a sample of 16 schools and 665 schoolchildren. The results show that Programa Huertas en Centros Educativos has a high positive impact on children's perception of the school and on their educational capabilities, while a relatively small impact is visible when focusing on diet quality and repetition of practices learned at school. One possible explanation for the lack of major benefits of the program on children's diet is a scarce community involvement, a feature deemed as crucial in similar interventions, and an insufficient integration of the program in the school curriculum.